Shared Socio-economic Pathways for European agriculture and food systems: the Eur-Agri-SSPs - Mitter, Hermine; Techen, Anja-K.; Sinabell, Franz; Helming, Katharina; Schmid, Erwin; Bodirsky, Benjamin L.; Holman, Ian P.; Kok, Kasper; Lehtonen, Heikki; Leip, Adrian; Le Mouël, Chantal; Mathijs, Erik; et al. (Elsevier, 2020)
Scenarios describe plausible and internally consistent views of the future. They can be used by scientists, policymakers and entrepreneurs to explore the challenges of global environmental change given an appropriate level of spatial and sectoral detail and systematic development. We followed a nine-step protocol to extend and enrich a set of global scenarios – the Shared Socio-economic Pathways (SSPs) – providing regional and sectoral detail for European agriculture and food systems using a one-to-one nesting participatory approach. The resulting five Eur-Agri-SSPs are titled (1) Agriculture on sustainable paths, (2) Agriculture on established paths, (3) Agriculture on separated paths, (4) Agriculture on unequal paths, and (5) Agriculture on high-tech paths. They describe alternative plausible qualitative evolutions of multiple drivers of particular importance and high uncertainty for European agriculture and food systems. The added value of the protocol-based storyline development process lies in the conceptual and methodological transparency and rigor; the stakeholder driven selection of the storyline elements; and consistency checks within and between the storylines. Compared to the global SSPs, the five Eur-Agri-SSPs provide rich thematic and regional details and are thus a solid basis for integrated assessments of agriculture and food systems and their response to future socio-economic and environmental changes
Keywords: Consistency; Integrated assessment; Land use; Narrative; Storyline development; Scenario